Unveiling Shadows: E-commerce and Modern Slavery - Legal Realities and Societal Implications - Sari, Rizqi Puspita; Mediawati, Noor Fatimah; Khumairoh, Bulqis (Proceedings of The ICECRS, 2023)
This data article details a systematic search on Lens.org, yielding documents related to "e-commerce AND modern slavery." Filtering for "journal articles" and "conference proceedings" resulted in a dataset available in CSV and BIBTEX formats. This resource enables comprehensive literature reviews, offering insights into the intersection of e-commerce and modern slavery, identifying existing research landscapes, potential gaps, and avenues for future exploration.Highlights : Systematic search on Lens.org for documents linking e-commerce and modern slavery. Dataset availability in CSV and BIBTEX formats for comprehensive reviews. Highlights insights, gaps, and avenues for further exploration in this critical issue. Keywords: e-commerce, modern slavery, data article, literature review, Lens.org